LEGAL ANALYSIS OF ABUSE OF AUTHORITY BY NOTARIES IN MAKING AUTHENTIC DEEDS - Aisyah Okta Setiani; Habib Adjie (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
A notary is a public official authorized by the state to create authentic deeds that have full evidentiary force before the law. However, in practice, notaries often abuse their authority in carrying out their duties, resulting in the loss of authenticity of the deed and causing losses to the parties. This study aims to analyze the forms of abuse of authority committed by notaries in creating authentic deeds, the resulting legal consequences, and the forms of legal accountability that can be imposed on notaries. The research method used is normative juridical, by examining applicable statutory provisions, legal doctrine, and relevant court decisions. The approaches used include a statutory approach, a conceptual approach, and a case approach. The results of the study indicate that abuse of authority by notaries can occur in various forms, including creating deeds without the presence of the parties, falsifying data, and providing false information in the deed. These actions not only violate the principles of professionalism and integrity of the notary's office, but also result in the deed losing its evidentiary force. Legal accountability for notaries who abuse their authority can take the form of administrative, civil, or criminal sanctions, depending on the level of error and the impact of their actions. To prevent recurrence of abuse of authority, it is necessary to strengthen the oversight system by the Notary Supervisory Board, improve moral integrity, and update the notary professional ethics education and training system. Keywords: Notary, Authentic Deed, Abuse of Authority, Legal Accountability, Professionalism